Intraocular Foreign Fody : A case Series - Purnama Sari, Mega Wulan; Sovani, Iwan; Kartasasmita, Arief; Iskandar, Erwin; Virgana, Rova; Ihsan, Grimaldi (International Journal of Retina, 2018)
Introduction: The incidence of Intraocular Foreign Body (IOFBs) among open-globe injuries ranges from 18% to 41%. In addition to clinical examination at the slit-lamp and indirect ophthalmoscopy, various imaging modalities are valuable for the identification and localization of IOFB. Vision loss can be devastating as a result of endophthalmitis, retinal detachment or proliferative vitreoretinopathy (PVR). Timely and appropriate management often leads to favorable anatomic outcomes with restoration of good visual function in the majority of cases. This case report presents the clinical and diagnostic finding, management, outcomes and further plan of the patients with posterior segment IOFB. Purpose: To report some cases of posterior segment intraocular foreign body. Case report: Three patients with history of ocular  trauma of the right eye that happened at workplace. All of patients were men in age range 20-55 years old . There were also loss of vision, pain, redness, and from ophthalmological examinations revealed two scleral injuries and one corneal injury that suggest an IOFB in posterior segment. Two patients were suggest endophtalmitis before operation. The plain x ray film examination showed intraocular foreign body in the right eyes. The Ultrasonography (USG) examination also showed intraocular foreign body in the right eyes. All of patient were underwent pars plana vitrectomy. Durante operation 2 of 3 patients were succeed to extract IOFB from the posterior segment, while one patient was not. Conclusion: Preoperative, intraoperative and postoperative management should be done correctly for some cases of IOFB. Prompt treatment and full assessment of patients is important to provide good prognosis.